2013
DOI: 10.1002/jcb.24433
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling nanotube formation is essential for the regulation of osteoclastogenesis

Abstract: Osteoclasts are the multinucleated giant cells formed by cell fusion of mononuclear osteoclast precursors. Despite the finding of several membrane proteins involving DC-STAMP as regulatory proteins required for fusion among osteoclast precursors, cellular and molecular events concerning this process are still ambiguous. Here we identified Tunneling Nanotubes (TNTs), long intercellular bridges with small diameters, as the essential cellular structure for intercellular communication among osteoclast precursors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 39 publications
3
59
0
Order By: Relevance
“…DC-STAMP is a major regulatory protein that required for fusion osteoclast precursors. Takahashi et al (2013) identified TNTs were the essential cellular structure for intercellular communication among osteoclast precursors in prior to cell fusion. They also detected that the rapid intercellular transport of the DC-STAMP-GFP fusion protein through TNTs formed among osteoclast precursors during osteoclastogenesis (Takahashi et al, 2013).…”
Section: Differentiation and Cellular Reprogrammingmentioning
confidence: 99%
See 2 more Smart Citations
“…DC-STAMP is a major regulatory protein that required for fusion osteoclast precursors. Takahashi et al (2013) identified TNTs were the essential cellular structure for intercellular communication among osteoclast precursors in prior to cell fusion. They also detected that the rapid intercellular transport of the DC-STAMP-GFP fusion protein through TNTs formed among osteoclast precursors during osteoclastogenesis (Takahashi et al, 2013).…”
Section: Differentiation and Cellular Reprogrammingmentioning
confidence: 99%
“…Takahashi et al (2013) identified TNTs were the essential cellular structure for intercellular communication among osteoclast precursors in prior to cell fusion. They also detected that the rapid intercellular transport of the DC-STAMP-GFP fusion protein through TNTs formed among osteoclast precursors during osteoclastogenesis (Takahashi et al, 2013). Moreover, these intercellular bridges are essential for differentiation of mesenchymal stem cells (MSCs) into cardiomyocytes or smooth muscle cells in vivo .…”
Section: Differentiation and Cellular Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…158 Recently, MNTs have been observed between MSCs and vascular smooth muscle cells (VSMCs), which promoted the proliferation but not differentiation of MSCs by transfer of mitochondria from VSMCs into MSCs, 178 as well as between MSCs and osteoclast precursors, which was found to be essential for osteoclastogenesis. 179 Overall, MNTs are novel candidates to explain how direct cell-to-cell communication occurs and play an important role in many (patho)physiological processes by transporting molecular signals and cell organelles from one cell to another. 180 We propose that communication through nanotubes could be an additional mechanism by which MSCs exert their positive effect in tissue regeneration.…”
Section: Membrane Nanotubesmentioning
confidence: 99%
“…Recently, MNTs observed between MSCs and vascular smooth muscle cells promoted the proliferation but not differentiation of MSCs by transfer of mitochondria [23], and MNTs between osteoclast precursors were found essential for osteoclastogenesis [33]. MNTs also exist between malignant tumor cells of mesothelioma and lung cancer and might play a critical role in tumor formation and development [7].…”
Section: Promotion Of Cell Biological Functionsmentioning
confidence: 99%